Applications of Computing, Automation and Wireless Systems in Electrical Engineering Proceedings of MARC 2018 - Mishra, Sukumar; Sood, Yog Raj.; Tomar, Anuradha; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses key concepts, challenges and potential solutions in connection with established and emerging topics in advanced computing, renewable energy and network communications. Gathering edited papers presented at MARC 2018 on July 19, 2018, it will help researchers pursue and promote advanced research in the fields of electrical engineering, communication, computing and manufacturing.
Fault detection in AC transmission system using Multiple Signal Classification technique -- Steady State Performance of DFIG with Stability Assessment in Wind System -- Comparison of two Design Methods of Triboelectric Nanogenerator for Building Efficient Energy Harvesting and Storage -- Maximization of Plug-in Electric Vehicle's Exploitation for load flattening with consideration of Customer Satisfaction -- A Novel Strategic Scheduling of Plug-in-Electric Vehicles to Reduce Power Fluctuations in an Active Distribution Network -- Design of an Effective Control Structure to Grid Interfaced Solar Inverter with Fault Stability Performance -- Whale Optimization Algorithm Tuned Fuzzy Integrated PI controller For LFC problem in Thermal-Hydro-Wind Interconnected System -- Mamdami based FuzzyPI controller tuned by Binary GWO Technique for LFC problem in Solar-thermal interconnected System.
Keywords: Electric power production; Multibody systems; Vibration; Mechanics, Applied; Telecommunication; Electrical Power Engineering; Multibody Systems and Mechanical Vibrations; Communications Engineering, Networks